The history of Portuguese interior plaster coatings: A mineralogical survey using XRD - Freire, T. (2015)
The evolution of the materials used in Portuguese interior wall coatings since the Roman occupation, namely the binders, is investigated using XRD in order to build a preliminary systematic database to contribute to the design and study of compatible products for conservation and repair. The results show that lime was the main binder until the end of the 18th century, with gypsum overcoming its use in the 19th century. A relationship is established between the results and several influencing aspects, namely other cultures, the neighbouring countries and their traditional construction techniques, the availability of raw materials, the purposes/techniques of application and the geographical location.